(untitled) (Journal of Shaheed Suhrawardy Medical College, 2017)
Background: Fibrocalculous pancreatic diabetes (FCPD) is a unique form of diabetes secondary to nonalcoholic, chronic, calcific, pancreatitis seen in tropical, developing countries of the world. Objective: The purpose of the present study was to determine the clinical features & the glycemic status of the children and adolescents with FCPD. Methodology: This descriptive study was undertaken in the department of paediatrics and at the data retrieval centre of Bangladesh Institute of Research and Rehabilitation in Diabetic, Endocrine and Metabolic Disorders (BIRDEM). Result: Among Seventy two cases of FCPD patients, majority (69.4%) of the patients were between 11-15 years age group and most (81%) of the study population were female. Most (68%) of them came from rural areas and belongs to lower socioeconomic class. Important clinical presentations were typical symptoms of diabetes mellitus (70.83%), abdominal pain (68.1%) and chronic diarrhoea (36.11%). The study population had poor glycaemic control, their mean ( SD) HbAlc were 16.58 4.07. Cataract was the most common complication (47.2%). Only one patient developed Diabetic Keto Acidosis (DKA). Conclusion: Majority of FCPD were female coming from rural areas with poor socio- economic. J Shaheed Suhrawardy Med Coll, 2014; 6(2):53-56